2009
DOI: 10.1002/ase.108
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Clinical Correlates in Anatomy: Design and implementation of a first‐year medical school program

Abstract: Medical students state the need for a clinically oriented anatomy class so to maximize their learning experience. We hypothesize that the first-year medical students, who take the Surgical Clinical Correlates in Anatomy program, will perform better than their peers in their anatomy course, their surgical clerkships and ultimately choose surgical residencies. We designed and recently implemented this program for first-year medical students. It consisted of General Surgical Knowledge, Orthopedic Surgery, Plastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 12 publications
(11 reference statements)
1
30
0
Order By: Relevance
“…A similar use of clinical procedures was piloted as a supplement to an anatomy course (Haubert et al, 2009). Their survey instrument revealed that students liked the supplement, but those who participated did no bet- Postclerkship examination of long-term effectiveness: subscores categorized by region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar use of clinical procedures was piloted as a supplement to an anatomy course (Haubert et al, 2009). Their survey instrument revealed that students liked the supplement, but those who participated did no bet- Postclerkship examination of long-term effectiveness: subscores categorized by region.…”
Section: Discussionmentioning
confidence: 99%
“…These challenges have been faced with varying success by a number of medical schools that experimented with the design of their anatomy course . One general approach has been to use the radiographic, medical, and surgical applications of anatomy to guide the structure and content of the course (McLachlan et al, 2004;Drake, 2007;Haubert et al, 2009). Examination of the efficacy of these approaches has been limited to preliminary studies.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the attending surgeons led students through related operative procedures on cadavers. The topics or specialties covered over the eight sessions included: cardiothoracic surgery, plastic surgery, general surgical knowledge, urology, general surgery, orthopedic surgery, vascular surgery, and ENT (Haubert et al, 2009). During these sessions, the students could perform surgery on the cadavers with the guidance of the surgeon.…”
Section: Five Programs To Engage Surgeons As Preclinical Teachersmentioning
confidence: 99%
“…Medical schools in Australia, New Zealand, Kuwait, and Saudi Arabia have also started CD as a voluntary activity [62-64]. Ohio State University in the USA has implemented elective programs with interactive CD for medical students in different surgical specialties [65]. Charles University in Prague, Czech Re­public, uses cadavers for teaching practical endoscopic methods to undergraduate and postgraduate students [66].…”
Section: Current State Of CD In Medical Trainingmentioning
confidence: 99%